2006
DOI: 10.1159/000089299
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Activated Form of Glycoproteins IIb/IIIa Complex on Newborn Platelets

Abstract: Background: GPIIb/IIIa complex is one of the laboratory markers of platelet activation. Closely associated with this process is exposure of the fibrinogen-binding site which is essential for platelets aggregation. This study was performed to evaluate the expression of GPIIb/IIIa on the platelets at time of birth. Materials and Methods: 51 term newborns, 21 females and 30 males, were introduced to the study. They fitted all criteria for healthy term newborns. Blood was collected from umbilical artery and vein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Since the surface expression of integrin αIIbβ3 is a good marker for platelet activation, these variations are probably due to differences in sample acquisition and preparation. In one study lower surface levels of the marker have been found, while another study found significantly higher values arguing for thrombogenesis during birth (8,9). Poor response to epinephrin might be caused by lower levels of α 2 -adrenergetic receptors (10).…”
Section: Vergleichende Bestimmung Des Gehalts Von Par1 Gpib-ix-v Anmentioning
confidence: 95%
“…Since the surface expression of integrin αIIbβ3 is a good marker for platelet activation, these variations are probably due to differences in sample acquisition and preparation. In one study lower surface levels of the marker have been found, while another study found significantly higher values arguing for thrombogenesis during birth (8,9). Poor response to epinephrin might be caused by lower levels of α 2 -adrenergetic receptors (10).…”
Section: Vergleichende Bestimmung Des Gehalts Von Par1 Gpib-ix-v Anmentioning
confidence: 95%
“…Therefore, the results should be interpreted with caution. 37 Of interest, Caparr ós-P érez et al performed a platelet transcriptome analysis and showed variations in the neonatal platelet transcriptome compared with adults. 38 In fact, they reported that genes involved in cell signaling and calcium metabolism were among those most downregulated in neonatal platelets.…”
Section: Activation Responses Of Fetal/neonatal Plateletsmentioning
confidence: 99%